The Brief study on the Human Nail (International Journal of Innovative Research in Computer Science & Technology, 2022)
A nail is a structure which is not a bone  made up of different composition than skin tissue like  keratin which is also found in hair and this is also shown  as an outer layer of skin for protection. Nail used to protect  finger tips and surrounding tissues from injury. The  epithelial matrix cells adhering to the nail bed give rise to  the development of nails. There is a difference between  healthy and unhealthy nails which is recognizable by their  difference in color, healthy nails are pink in color and have  a flexible smooth and glossy surface of nail. When it comes  to growth the development of nails is an indication of  eliminating dead cells from the human body. The growth  rate of nails are higher in children than young and elderly  adults. Human nails and issues connected with it such as  size, color and form of the nail will also reveal the kind of  illness and problems associated with the body. Human  nails consist of numerous components which have been  described in this article and also nails utilized to  accomplish different jobs are also detailed in this paper.  Human nails may act as an indication and it is a very useful  method for the treatment of various illnesses. In this paper  also discussed the purpose of the study which is to measure  the ph level of the nail and maintain healthy nail, to  maintain the healthy nail we have to measure the ph level  of nail paint and other nail related chemicals so that it can  give a healthy and shiny nail plates, in this paper on the  basis of healthy ph value of nail plate people can control  the flow of nail paint and nail paint remover on it. Also, the scope of the invention and why taking care of nail and  nail related treatments and issues has been addressed in  this paper, how we can maintain or raise or reduce the PH level of nail has also been mentioned in this paper.
Keywords: Acetone; Chemicals; Eponychium; Hyponychium; Lunula